Sotorasib in KRAS G12C-mutated non-small cell lung cancer: a multicenter real-world experience from the compassionate use program in Germany - Stratmann, Jan A.; Althoff, Friederike Cornelia; Doebel, Paula; Rauh, Jacqueline; Trummer, Arne; Hünerlitürkoglu, Ali Nuri; Frost, Nikolaj; Yildirim, Hüsameddin; Christopoulos, Petros; Burkhard, Oswald; Büschenfelde, Christian Meyer zum; Becker von Rose, Aaron; et al. (European journal of cancer, 2024)
Background - Sotorasib is a first-in-class KRAS p.G12C-inhibitor that has entered clinical trials in pretreated patients with non-small cell lung cancer (NSCLC) in 2018. First response rates were promising in the CodeBreaK trials. It remains unclear whether response to sotorasib and outcomes differ in a real-world setting when including patients underrepresented in clinical trials. - Methods - Patients with KRAS p.G12C-mutated advanced or metastatic NSCLC received sotorasib within the German multicenter sotorasib compassionate use program between 2020 to 2022. Data on efficacy, tolerability, and survival were analyzed in the full cohort and in subgroups of special interest such as co-occurring mutations and across PD-L1 expression levels. - Results - We analyzed 163 patients who received sotorasib after a median of two treatment lines (range, 0 to 7). Every fourth patient had a poor performance status and 38% had brain metastases (BM). The objective response rate was 38.7%. The median overall survival was 9.8 months (95% CI, 6.5 to not reached). Median real-world (rw) progression-free survival was 4.8 months (9% CI, 3.9 to 5.9). Dose reductions and permanent discontinuation were necessary in 35 (21.5%) and 7 (4.3%) patients, respectively. Efficacy seems to be influenced by PD-L1 expression and a co-occurring KEAP1 mutation. KEAP1 was associated with an inferior survival. Other factors such as BM, STK11, and TP53 mutations had no impact on response and survival. - Conclusion - First results from a real-world population confirm promising efficacy of sotorasib for the treatment of advanced KRAS p.G12C-mutated NSCLC. Patients with co-occurring KEAP1 mutations seem to derive less benefit.
Online verfügbar: 14. Februar 2024, Artikelversion: 19. Februar 2024
Gesehen am 24.09.2024